NEW INFORMATION TECHNOLOGIES FOR THE ELECTRONIC GOVERNMENT IN UKRAINE - Lyubich, Oleksandr; Pleskach, Valentyna (Journal of European Economy, 2018)
The article defines the essence of the task of forming the e-government in Ukraine and provides schemes of electronic governance. The authors examine the approaches to the concept of e-government development by applying new information technologies in Ukraine and conduct a comparative analysis of foreign experience. Finally, the authors determine the objective of e-government formation and its functioning in Ukraine.